Penentuan Remaining Service Life Struktur Conveyor A pada Tambang Batubara PT GHI di Kabupaten Tapin Kalimantan Selatan - Ardiansyah; Elfida Moralista (UNISBA Press, 2022)
Abstract. Conveyor is a means of transportation commonly used in the mining industry. Part of thestructure is conveyor made of carbon steel which makes it easy to corrode. So that it can affect the remaining design life of thestructure conveyor. The purpose of this study is to determine the type of corrosion and to determine the corrosion control with themethod coating of the structure conveyor. The method used in this research is thickness measurement which includes nominal thickness and actual thickness. The research was conducted on the structure conveyor by using three segments, 25 test points with alength of conveyor 90 m. The air temperature in the study area ranges from 30,88 0C – 37,23 0C, with rainfall of 27,6 mm/year. The type of corrosion that occurs in the conveyor structure is the type of uniform corrosion. Corrosion control is carried out using the coating method. Primer coating using Seaguard 5000, Intermediate coating using Shear Glass FF and Top coating using Aliphatic Acrylic Modified Polyurethane. Abstrak. Conveyor merupakan alat angkut yang biasa digunakan dalam industri pertambangan. Bagian dari struktur conveyor terbuat dari baja karbon yang menjadikannya mudah untuk terkorosi. Sehingga dapat mempengaruhi sisa umur desain dari struktur conveyor tersebut. Tujuan dari penelitian ini yaitu untuk mengetahui jenis korosi dan mengetahui pengendalian korosi dengan metode coating pada struktur conveyor. Metode yang digunakan dalam penelitian ini yaitu pengukuran ketebalan yang meliputi tebal nominal dan tebal aktual. Penelitian dilakukan pada struktur conveyor yaitu dengan menggunakan tiga segmen, 25 test point dengan panjang conveyor 90 m. Temperatur udara yang ada pada daerah penelitian berkisar antara 30,88 oC – 37,23 oC, dengan curah hujan 27,6 mm/tahun. Jenis korosi yang terjadi pada struktur conveyor adalah jenis korosi merata. Pengendalian korosi yang dilakukan dengan menggunakan metode coating. Primer coating menggunakan Seaguard 5000, Intermediete coating menggunakan Shearglass FF dan Top coating menggunakan Alipatic Acrilic Modified Polyuerethane.